Circular RNAs in cancer: Limitations in functional studies and diagnostic potential. (October 2021) - Li, Feiya; Yang, Qiwei; He, Alina T.; Yang, Burton B.
Abstract: Circular RNAs (circRNAs) are a large class of noncoding RNAs, generated from a process called back-splicing, that possess critical regulatory functions in many cellular events. A large body of literature has reported various circRNA functions and their underlying mechanisms, including sponging miRNA, exerting transcriptional and translational regulation, interacting with proteins, and translating into peptides and proteins. CircRNA dysregulation has been implicated in many cancers, including lung, breast, liver, gastric, colorectal, and ovarian cancer. They are detectable in bodily fluids and relatively stable, making them potential cancer biomarker candidates. Furthermore, targeting circRNA expression levels is a potential therapeutic approach for treating cancers. In this review, we describe the functional mechanisms of circRNAs and discuss limitations of current mechanism studies. Following this, we outline the potential of circRNAs to be effective biomarkers in various cancers and present circRNA-based therapeutic approaches. Finally, we discuss challenges in using circRNAs as diagnostic and therapeutic tools and propose future research directions.